Investigations of touchscreen glasses from mobile phones for retrospective and accident dosimetry. (June 2016) - Discher, Michael; Bortolin, Emanuela; Woda, Clemens
Abstract: Touchscreen glasses of mobile phones are sensitive to ionizing radiation and have the potential of usage as an emergency dosimeter for retrospective dosimetry for the purpose of triage after a radiological accident or attack. In this study the TL glow curves and dosimetric properties of touchscreen glasses were studied in detail, such as intrinsic background dose, dose response, reproducibility, optical stability and long-term stability of the TL signal. Preliminary results are additionally presented to minimize the intrinsic background dose by mechanically removing the surface layer of the glass samples. Additionally chemical element analyses of the touchscreen glass samples were carried out to investigate the difference between glass samples which show a TL signal and samples which show neither an intrinsic zero dose signal nor a radiation induced TL signal. An irradiation trial using glass samples stored in the dark demonstrated a successful dose recovery. However, when applying a realistic, external light exposure scenario, dose underestimation was observed, even though samples were pre-bleached prior to measurement. More investigations have to be carried out in the future to solve the challenge of the low optical stability of the TL signal, if touchscreen glasses are to be used as a reliable emergency dosimeter. Highlights: Touchscreen glasses are sensitive to ionizing radiation and show suitable dosimetric properties. Mechanically treated samples demonstrated a significant reduction of the intrinsic zero dose signal. An irradiation trial showed limitations of the used protocol for strongly bleached samples.